International order in a globalizing world [ - Stivachtis, Yannis A. , 1965- (Global interdisciplinary studies series, 2007)
International order shapes, and is also being shaped by, the forces of globalization, whether cultural, political or economic. This volume examines issues that transcend national and cultural boundaries. It discusses international order from the perspective of the English School of International Relations, and ultimately analyzes what is to be done to assure a stable international order